K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 4 2018

= [ 60/90 - ( 12/15 + 10/15) ] : 6/5

= ( 2/3 - 22/15 ) x 5/6

= ( 10/15 - 22/15 ) x 5/6

= -12/15 x 5/6

= -60/90

= -2/3

25 tháng 4 2018

( 15/10 x 4/9 - ( 4/5 + 2/3 )) : 6/5

( 15/10 x 4/9 - ( 12/15 + 10/15 )) : 6/5

(30/45 - 66/45 ) : 6/5

-12/15 : 6/5 ( đã rút gọn -36/45 = -12/15 )

-2/3

k mk na <3

3 tháng 4 2016

đáp án :19/12

10 tháng 8 2016

a) \(\frac{1}{3}.\frac{-6}{13}.\frac{-9}{10}.\frac{-13}{36}\)

\(=\left(\frac{1}{3}.\frac{-9}{10}\right)\left(\frac{-6}{13}.\frac{-13}{36}\right)\)

\(=\frac{-3}{10}.\frac{1}{6}\)

\(=\frac{-1}{20}\)

b) \(\frac{-1}{3}.\frac{-15}{17}.\frac{34}{45}\)

\(=\frac{-1}{3}.\frac{-2}{3}\)

\(=\frac{2}{9}\)

c) \(\left(1-\frac{1}{5}\right)\left(\frac{-3}{10}+\frac{1}{5}\right)\)

\(=\frac{4}{5}.\frac{-1}{10}\)

\(=\frac{-2}{25}\)

d) \(A=\frac{1}{3}.\frac{4}{5}+\frac{1}{3}.\frac{6}{5}+\frac{2}{3}\)

\(=\frac{1}{3}\left(\frac{4}{5}+\frac{6}{5}\right)+\frac{2}{3}\)

\(=\frac{1}{3}.2+\frac{2}{3}\)

\(=\frac{2}{3}+\frac{2}{3}\)

\(=\frac{4}{3}\)

e)  \(11\frac{1}{4}-\left(2\frac{5}{7}+5\frac{1}{4}\right)\)

\(=\left(11\frac{1}{4}-5\frac{1}{4}\right)-2\frac{5}{7}\)

\(=6-2\frac{5}{7}\)

\(=5\frac{7}{7}-2\frac{5}{7}\)

\(=3\frac{2}{7}\)

9 tháng 6 2017

Theo đề ta có:

\(\left(5+\frac{1}{5}-\frac{2}{9}\right)-\left(2-\frac{1}{23}-2\frac{3}{5}+\frac{5}{6}\right)\)\(-\left(8-\frac{2}{3}-\frac{1}{18}\right)\)

= \(5+\)\(\frac{1}{5}-\frac{2}{9}\)-\(2+\frac{1}{23}+2+\frac{3}{5}+\frac{5}{6}-8+\frac{2}{3}-\frac{1}{18}\)

=\(\left(5+2-8\right)+\left(\frac{1}{5}+\frac{3}{5}\right)-\left(\frac{2}{9}-\frac{5}{6}-\frac{2}{3}+\frac{1}{18}\right)+\frac{1}{23}\)

=  -1 +\(\frac{4}{5}\)\(-\frac{-11}{9}\)+\(\frac{1}{23}\)

= -1 +\(\frac{4}{5}+\frac{11}{9}+\frac{1}{23}\)

10 tháng 6 2017

\(\left(5+\frac{1}{5}-\frac{2}{9}\right)-\left(2-\frac{1}{23}-2\frac{3}{5}+\frac{5}{6}\right)-\left(8-\frac{2}{3}-\frac{1}{18}\right)\)

\(5+\frac{1}{5}-\frac{2}{9}-2+\frac{1}{23}+2+\frac{3}{5}-\frac{5}{6}-8+\frac{2}{3}+\frac{1}{18}\)

\(\left(5-8\right)+\left(\frac{1}{5}+\frac{3}{5}\right)-\left(\frac{2}{9}-\frac{1}{18}-\frac{2}{3}\right)-\left(2-2\right)+\frac{1}{23}-\frac{5}{6}\)

\(\left(-3\right)+\frac{4}{5}+\frac{1}{2}+\frac{1}{23}-\frac{5}{6}\)

\(\left(\left(-3\right)+\frac{4}{5}+\frac{1}{2}-\frac{5}{6}\right)+\frac{1}{23}\)

\(-\frac{38}{15}+\frac{1}{23}\)

\(-\frac{859}{345}\)